Генетска варијабилност и критеријуми селекције неких сезамових генотипова због њихових агрономских особина и квалитета семена - Abdelsatar, Mohamed Ali (Journal of Agricultural Sciences (Belgrade), 2021)
Study of mean performance, genetic parameters and selection criteria of twelve sesame genotypes for agronomic traits and seed quality were the main objective of this stud. These genotypes were evaluated in a field trial at Kafr-El-Hamam Agricultural Research Station, ARC, Sharkia Governorate, Egypt and laboratory experiments at of Seed Technology Research Department, ARC, Giza, Egypt during the two successive seasons 2018 and 2019 using a randomized complete block design with three replications. The promising genotypes were N.A.130 and Shandweel-3 for earliness in flowering, and N.A.114 and RH1F3 possessed the heaviest weight of seed plant-1 and one or more of yield related traits as well as NA114, Shandweel-3 and Zahar12 for most seed quality traits, in addition Shandweel-3 and M1A12 for seed oil content, Shandweel-3 and Zahar12 for oleic, NA 114 and RH1F3 for linoleic and Zahar12 and NA 114 for linolenic. Seed weight plant-1 can be improved through selecting genotypes having the lengthiest fruiting zone, more branches, capsules, the heaviest weight of 1000-seed and seedling dry weight, and the high electrical values of seed conductivity, accelerated ageing germination as proven by selection criteria. Moreover, oleic acid content had the highest direct and indirect effect on seed oil content indicating their importance as selection criteria to oil quality of sesame.